2006
DOI: 10.1016/j.postharvbio.2006.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Sweetpotato cultivars differ in efficiency of wound healing

Abstract: This paper presents a study on the wound healing processes in sweetpotatoes (Ipomoea batatas Lam.) when exposed to tropical conditions typical for marketing (RH 50% to 73%, T 25ºC to 30ºC). The physiological processes during healing are revisited. Under sub-optimal humidities (65% 10) the depth of the lignified layer i.e. the thickness of the desiccated cell layers is affected by both cultivar and humidity. Some cultivars consistently failed to produce a lignified layer and for others the layer is often not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 19 publications
0
19
0
2
Order By: Relevance
“…The variability in wound healing efficiency is attributed to the difference in dry matter content. Dry matter content of sweetpotato cultivars inversely relates with lignification score, an index for wound healing (van Oirschot et al 2006). Thus, cultivars with low dry matter content heal their wounds better than those with high dry matter content.…”
Section: Wound Healing Scorementioning
confidence: 99%
See 2 more Smart Citations
“…The variability in wound healing efficiency is attributed to the difference in dry matter content. Dry matter content of sweetpotato cultivars inversely relates with lignification score, an index for wound healing (van Oirschot et al 2006). Thus, cultivars with low dry matter content heal their wounds better than those with high dry matter content.…”
Section: Wound Healing Scorementioning
confidence: 99%
“…The objective of the study was to assess the wound healing and changes in dry matter content of two OFSP cultivars has been associated with good root storage (van Oirschot et al, 2006). However, wound healing ability has been previously reported to vary greatly among cultivars (van Oirschot et al 2006) and to be inversely correlated to dry matter content .…”
Section: Wound Healing Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Wound periderm, which is similar to native periderm, forms best at 28 to 30°C and relative humidity above 85% (Kushman and Wright, 1969). Wound healing has been negatively correlated with decreased dry matter content (van Oirschot et al, 2006) and positively correlated with increased sugar levels at the wound site (Rees et al, 2008). van Oirschot et al (2006) found that the thickness of the desiccated cell layer and the depth of the lignified layer are affected by cultivar and humidity.…”
mentioning
confidence: 99%
“…Wound healing has been negatively correlated with decreased dry matter content (van Oirschot et al, 2006) and positively correlated with increased sugar levels at the wound site (Rees et al, 2008). van Oirschot et al (2006) found that the thickness of the desiccated cell layer and the depth of the lignified layer are affected by cultivar and humidity. Lignified layers are not always produced (or discontinuous) in some cultivars and continuity is more important than thickness (van Oirschot et al, 2006).…”
mentioning
confidence: 99%